Resolusi Konflik Perebutan Mayat: Negosiasi Antaragama di Sentani, Papua - Faisal, Faisal; Zulfadli, Zulfadli; Puarada, Fajrul Ramadan (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
This study examines the social dynamics of the muallaf community in Sentani, focusing on religious and familial conflicts during funeral processes. The aim is to explore how family disputes arising from differing religious beliefs can be mitigated through power-sharing negotiation strategies. Employing a qualitative methodology with a phenomenological approach, the research utilizes Jackman's negotiation theory as an analytical framework. Data were collected through observations, interviews, and documentation involving religious leaders and family members. Findings indicate that effective mediation and open communication are key strategies in alleviating tensions. Additionally, the roles of government and religious organizations are critical in maintaining order, mediating disputes, and formulating inclusive policies. Religious leaders contribute by enforcing ethical norms, providing counseling, and facilitating negotiations. Collaborative efforts between government and religious institutions can yield fair solutions that respect various traditions. By fostering inclusivity and mutual respect for diverse customs, communities can create a more harmonious environment. This study recommends enhancing conflict resolution knowledge and developing innovative strategies to address future challenges effectively.